PELATIHAN PENULISAN ARTIKEL POPULER UNTUK MENUNJANG KENAIKAN PANGKAT BAGI GURU DI SMAN 4 BANDAR LAMPUNG - Nirwana Hendrastuty; M. Ghufron An’Ars; Damayanti Damayanti; Selamet Samsugi; Musa Paradisiaca; Samuel Hutagalung; Anton Mahendra (Universitas Teknokrat Indonesia, 2022)
Popular scientific work is often interpreted as a written work made based on a scientific rule with the aim that all discussions can be understood by various general groups or not only academics. There are so many benefits that can be felt by teachers from writing popular articles, by writing popular articles the teacher can share knowledge with anyone through his writings, can motivate students. And to take care of promotions for teachers, one of them is promotion. The promotion for teachers is one way to improve achievement and ensure welfare. one of the elements of promotion of teachers from certain groups to a higher class one of the supporters is to make written works published in mass media such as newspapers, magazines, or online media on official websites. According to data released by Kompas, the number of teachers in Indonesia currently reaches 2,698,103. Unfortunately, of the number of teachers who are able to produce a written work is very minimal. This can be proven by the number of written works published by the teacher. This problem is also experienced by SMKN 4 Bandar Lampung, teachers who do not teach Indonesian still find it difficult and confused to determine ideas from popular scientific articles. Based on the partner problems above, our team agreed to provide solutions to partner problems, namely by providing opinion writing training especially for teachers at SMKN 4 Bandar Lampung. At the time of training, teachers are asked to think of ideas that will be used as popular scientific works and to jointly correct the results of scientific writings from each teacher.